2018
DOI: 10.1590/0001-3765201820170399
|View full text |Cite
|
Sign up to set email alerts
|

Fruits of the Brazilian Atlantic Forest: allying biodiversity conservation and food security

Abstract: Supplying food to growing human populations without depleting natural resources is a challenge for modern human societies. Considering this, the present study has addressed the use of native arboreal species as sources of food for rural populations in the Brazilian Atlantic Forest. The aim was to reveal species composition of edible plants, as well as to evaluate the practices used to manage and conserve them. Ethnobotanical indices show the importance of many native trees as local sources of fruits while high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 18 publications
0
12
0
9
Order By: Relevance
“…With the exception of zeaxanthin, they are the most commonly found in food, with β-carotene being the most widely distributed ( Rodriguez-Amaya et al., 2008 ). It is important to highlight the relevance of recognizing these sources of carotenoids in fruits to increase their consumption by the population and stimulate their cultivation, since fruit trees play an important economic role for the Brazilian population and local industries, although they are still under-explored ( Ribeiro et al., 2014 ; Souza et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of zeaxanthin, they are the most commonly found in food, with β-carotene being the most widely distributed ( Rodriguez-Amaya et al., 2008 ). It is important to highlight the relevance of recognizing these sources of carotenoids in fruits to increase their consumption by the population and stimulate their cultivation, since fruit trees play an important economic role for the Brazilian population and local industries, although they are still under-explored ( Ribeiro et al., 2014 ; Souza et al., 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that harvesting and domesticating various fruit plants emerge significant economic benefits (Agbelade & Onyekwelu, 2013;Man & Januszewska, 2010;Onyekwelu, Olusola, Stimm, Mosandl, & Agbelade, 2014). Besides, forest fruit plants also provide ecological benefits for species conservation (Bolakhe & Ghimire, 2019;Estoque et al, 2019;De Souza et al, 2018) and the environment (Khair, Purnomo, & Sumaryoto, 2017;Sardeshpande & Shackleton, 2019;Wang, Sun, Xiong, Yang, Hou, & Sheng, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is one of the main fresh fruit producers worldwide because of its favorable climatic conditions. Some recent studies have shown that the biomes of the Brazilian territory include a variety of native and exotic species that could be used in food (Souza et al, 2018;Teixeira et al, 2019) to improve its nutritional value and provide health benefits owing to the presence of a great diversity of bioactive chemical compounds (Paz et al, 2015). However, information on this potential of some species is not only limited, but completely absent.…”
Section: Introductionmentioning
confidence: 99%